Asia's international production networks: Will India be the next assembly centre? - Rahul Sen; Sadhana Srivastava (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2012)
This paper analyses the current state of participation of India in the international production networks (IPNs) of manufacturing industries in Asia, and identifies the constraints and challenges for India's deeper participation in the near future. Using the disaggregated 5 digit SITC (Rev 3) level data, the estimates of intra-industry trade and export revealed comparative advantage in Parts and Components (P&C) in India's manufacturing sector are analysed separately from that of total trade flows over the period from 1994 and 2008. This provides useful insights into the nature and magnitude of production fragmentation involving Foreign Direct Investment (FDI). The analysis demonstrates that India has reoriented its growth strategy, towards an outward orientation, during the past two decades, but the pace of its reform has not caught up with this paradigm shift. As a result, the level of participation by Indian industries in global and in Asian IPNs is low. Most of India's exports comprise lowtechnology, labour-intensive goods that do not involve much fragmentation, such as textiles, gems and jewellery and animal and leather products. Five key policy recommendations are proposed, based on the current state of India's participation in IPNs and the associated policy challenges. It is particularly noted that India's existing Preferential Trade Agreements (PTAs) do not appear to be designed with the objective of reducing the costs involved in setting up an IPN. A critical review is therefore required of India's current PTAs, including more inputs from businesses, to identify specific areas of gains from PTAs in order to create a business environment that would make India a potential assembly centre for global manufacturing activities in the near future. Implementation integrity and effective utilization of PTAs involving India and member countries will also be a key to whether PTAs will be successfully able to play a role in plugging India into global and Asian IPNs.
Keywords: F13; F14; F23; 330; India; international production networks; intra-industry trade; Asia; PTAs; Unternehmensnetzwerk; Multinationales Unternehmen; Verarbeitendes Gewerbe; Außenhandelspräferenz; Intraindustrieller Handel; Indien